Overhead Transmission Lines Deicing under Different Incentive Displacement - Qing He; Xi-feng Lv; Xiao-tong Zhao (Journal of Applied Mathematics)
Overhead transmission line icing is one of the main factors affecting safety and reliability of power grid. This paper proposed an excitation deicing method of iced wire and theoretically revealed the ice removal mechanism under displacement excitation conditions, by taking the LGJ-70/10 glaze icing wire as the 3D model and analyzing and studying its dynamic response under the effect of displacement excitation. The simulation results show that the stress of wire icing area is enlarged with the increase of excitation displacement and frequency. Through the comparison of the compression strength experimental results on a series of different iced wires in low temperature environment, the authors found out that the stress generated from the wire icing area is greater than the crushing strength of the ice within the scope of the calculation parameters, which proved the validity and the feasibility of the method, and finally the suitable excitation displacement is determined. Following studies show that, as far as possible, it is necessary to reduce the incentive displacement and also to select the appropriate constraint length in order to avoid the line jumping that may be caused by large span ice shedding.